O mundo segundo o mito: o perspectivismo ameríndio e a virada ontológica - Campelo, Wendel de Holanda Pereira (2023)
This work seeks to contribute to the debate on the so-called ontological turn in philosophy and anthropology, particularly with regard to reality or with the world in itself, instead of an approach that only favours categories such as language, cognition, culture, etc. From this perspective, the focus of this work is the mythical thought of the Amerindian peoples, and discusses some problems raised in the work A inconstância da alma selvagem (2002) and Metafísicas Canibais (2018) by Viveiros de Castro, in dialogue with authors such as Danowski (2014) and Meillassoux (2008). Specifically, this research seeks to offer an ecology of knowledge between materialist ontology, associated with science in hegemonic terms, and Amerindian perspectivism, linked to the mythology of indigenous peoples. In this way, it was argued that Amerindian thought is promising as an ontology and an epistemology capable of meeting the requirements of a post-abyssal and cosmopolitical thought.